Estudo Mecanístico da Eletrodeposição de Cádmio em Meio de Sulfato Ácido - Campos, Othon Souto (2011)
This work describes a mechanistical proposition for cadmium electrodeposition in acid sulfate medium on platinum substrate using electrochemical techniques. The cadmium electrodeposition studies were carried in sodium sulfate 1 mol L–1 medium containing cadmium sulfate 10–2 mol L–1, which the pH of the solutions were adjusted with analytical grade sulfuric acid. The pH interval of the work solutions were ranged between 1 and 3. In all studied medium, the potentiostatic polarization curves showed a diffusional plateau which obeys the Levich equation. The interfacial pH studies showed the influence of acid–base equilibrium of bisulfate ion with the formation of a coordination compound Cd(HSO4)+ in platinum electrode. It is proposed that the cadmium ion associated in acid–base equilibrium of bisulfate ion, deposits as cadmium bisulfate at an irreversible step, and followed by a reversible metallic deposition of cadmium with the leaving of bisulfate ion, and this step is slower than the first one. Then, a mathematical model was calculated for the mechanism proposed, and qualitative studies were carried regarding to the polarization curve and electrochemical impedance spectroscopy behavior